Wheat Grain Yield and Protein Response to Nitrogen and Sulfur Rates - B. R. Jaenisch; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2019)
Winter wheat is often double-cropped after soybeans in no-tillage systems. The soybean crop removes large quantities of sulfur (S), which might unbalance ratios of nitrogen (N) to S for the following wheat crop. Our objective was to evaluate the responses of two wheat varieties to three N and four S rates representing a range of N:S ratios. The experiment was arranged as a complete factorial with a split-split-plot design. Variety was the whole-plot, N the sub-plot, and S the sub-sub plot. Nitrogen rates were 50, 100, and 150% of the recommended rate for 60 bu/a, which corresponded to ~45, 87, and 130 lb N/a. Sulfur rates were 0, 10, 20, and 40 lb S. The two locations (Manhattan and Belleville) were conducted under no-till and data were pooled for the statistical analysis. Nitrogen by S interactions occurred for grain yield and protein. The 45 lb N/a with 0, 10, or 40 lb S yielded similarly, while 20 lb S reduced yield by 4 bu/a. The 87 lb N/a increased yield by 9 bu/a from the 45 lb N/a with all S rates yielding similarly. The 130 lb N/a increased yield by 18 bu/a from the 45 lb N/a with 10 lb S resulting in the lowest yield, with 0 and 20 lb S yielding the highest. Zero and 40 lb S resulted in similar yields across all N rates. The 45 and 130 lb N/a with 10 lb S produced protein of 10.9% and 11.9%, respectively. However, 130 lb N/a with 0 or 10 lb S increased protein to 12.6–12.8%. This research will be continued for two more years at three locations per year to better explore the interactive effects of N, S, and variety.
Keywords: wheat; nitrogen; sulfur; yield; protein